2014
DOI: 10.1007/s13730-014-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in karyomegalic interstitial nephritis three years after ifosfamide and cisplatin therapy by corticosteroid

Abstract: Long-term nephrotoxicity of ifosfamide is occasionally progressive, and, in such case, there has been no specific treatment to prevent progression. It has been reported that the presence of karyomegalic interstitial nephritis, which is rare type of interstitial nephritis, may be related to ifosfamide-induced nephropathy with poor prognosis and resistant to the immunosuppressive therapy. A 15-year-old boy presented with progressive nephrotoxicity 3 years after systemic chemotherapy with ifosfamide and cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
(31 reference statements)
3
15
0
Order By: Relevance
“…Several studies have reported KIN in patients treated for childhood cancer as a rare event related to ifosfamide treatment, a nephrotoxic drug that is known to cause tubulopathy, reduced glomerular filtration and renal Fanconi syndrome, but details on clinical features and pathology are lacking. Matsuura et al, 2014;Jaysurya et al, 2016; Despite the small sample size, our observations confirm that tubular injury after ifosfamide therapy is responsible for the clinical picture and suggest that KIN and cellular senescence should be considered as underlying cause of early CKD in childhood cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have reported KIN in patients treated for childhood cancer as a rare event related to ifosfamide treatment, a nephrotoxic drug that is known to cause tubulopathy, reduced glomerular filtration and renal Fanconi syndrome, but details on clinical features and pathology are lacking. Matsuura et al, 2014;Jaysurya et al, 2016; Despite the small sample size, our observations confirm that tubular injury after ifosfamide therapy is responsible for the clinical picture and suggest that KIN and cellular senescence should be considered as underlying cause of early CKD in childhood cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…Tomokazu Matsuura et al reported a case of a 15-year-old boy presented with progressive nephrotoxicity 3 years after systemic chemotherapy with ifosfamide and cisplatin for the treatment of osteosarcoma. This case suggests the possibility that cisplatin may have a synergetic effect with ifosfamide for producing KIN [7].…”
Section: Discussionmentioning
confidence: 89%
“…described a 15-year-old boy who developed renal failure and fanconi's syndrome 3 years after receiving IFO. [ 3 ] In spite of significant chronicity in the biopsy, the patient showed improvement in GFR following corticosteroid therapy. It is postulated that IFO-induced DNA damage prevents the normal cellular regenerative process resulting in karyomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Later similar lesions were described in long-term survivors of malignancies treated with the alkylating agent ifosfamide (IFO). [ 2 3 ] To the best of our knowledge, only four cases of IFO-induced KIN (one case series and a single case report) have been published so far, and the optimal therapeutic strategies are unclear.…”
Section: Introductionmentioning
confidence: 99%